The rock coast of the British Isles: Weathering and biogenic processes - Coombes, M (Geological Society, 2014)
An abundance of moisture, salts and organic life make rock coasts a unique weathering environment. Here, mechanical and chemical processes act to break down rocks alongside the influence of waves, tides and geological factors. Organisms concurrently break down (bioweathering and bioerosion) and protect (bioprotection) coastal rocks in direct and indirect ways, enhancing or impeding other inorganic modes of decay. Some species also build physical structures (bioconstruction) that have geomorphological and ecological consequences. Studies of particular weathering processes are well represented in the British Isles, and demonstrate the overriding controls of lithology and tidal position. The complexities arising from the interactive and combined influences of different processes are also evident. Biogenic processes are of greatest importance for the geomorphology of carbonate rock coasts and cohesive shores in Britain and Ireland, but weathering is largely secondary to waves in the evolution of harder rock coasts. The importance of typically fine-scale rock decay in facilitating larger-scale erosion is recognised, however, but warrants more attention, and the value of interdisciplinary and applied weathering research on rock coasts is stressed.